Overtip Shock Wave Structure and Its Impact on Turbine Blade Tip Heat Transfer - Zhang, Q; O'Dowd, DO; He, L; Wheeler, A; Ligrani, P; Cheong, B (2011)
In this paper, the transonic flow pattern and its influence on heat transfer on a high-pressure turbine blade tip are investigated using experimental and computational methods. Spatially resolved heat transfer data are obtained at conditions representative of a single-stage high-pressure turbine blade (Mexit=1.0, Reexit=1.27×106, gap=1.5% chord) using the transient infrared thermography technique within the Oxford high speed linear cascade research facility. Computational fluid dynamics (CFD) predictions are conducted using the Rolls-Royce HYDRA/PADRAM suite. The CFD solver is able to capture most of the spatial heat flux variations and gives prediction results, which compare well with the experimental data. The results show that the majority of the blade tip experiences a supersonic flow with peak Mach number reaching 1.8. Unlike other low-speed data in the open literature, the turbine blade tip heat transfer is greatly influenced by the shock wave structure inside the tip gap. Oblique shock waves are initiated near the pressure-side edge of the tip, prior to being reflected multiple times between the casing and the tip. Supersonic flow within the tip gap is generally terminated by a normal shock near the exit of the gap. Both measured and calculated heat transfer spatial distributions illustrate very clear stripes as the signature of the multiple shock structure. Overall, the supersonic part of tip experiences noticeably lower heat transfer than that near the leading-edge where the flow inside the tip gap remains subsonic. © 2011 American Society of Mechanical Engineers.